On some boundary value problems for linear multidimensional hyperbolic equations of the second order - Aldashev , S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
For the linear hyperbolic equations \[_i,j=1^m+1 a_ij(x,x_m+1)u_x_ix_j+_i=1^m+1 a_i(x,x_m+1)u_x_i+c(x,x_m+1)u=0, \] \[x=(x_1,…,x_m), m≥2\] the correctness of multidimensional analogues of the problems of Darboux and Goursat is established and a theorem on the uniqueness of a solution of the Cauchy characteristic problem is proved.